Perlindungan Terumbu Karang Menurut UNCLOS 1982 (Studi Kasus Kerusakan Terumbu Karang oleh Kapal Pesiar M.V. Caledonian Sky di Raja Ampat) - Trimirza, Maretta; Ramlan, Ramlan; Repindowaty, Rahayu (Uti Possidetis: Journal of International Law, 2021)
Coral reefs and all the life contained in them are one of the most valuable natural assets. Various damages done by humans have caused damage to the ecosystem that marine resources are reduced. The case of the collision by the cruise ship M.V. Caledonian Sky in Raja Ampat is causing damage to coral reefs, it needs protection and responsibility. This study aims to: First, identify and analyze how the protection of the marine environment against coral reefs is caused by the M.V. Cruise Ship. Caledonian Sky based on international law and national law. Second, knowing and analyzing how the M.V. Caledonian Sky for damage to coral reefs based on UNCLOS 1982 and national laws. The research method used is normative juridical research, by examining document studies using a variety of secondary data or library materials. The results of this study are First, protection of the marine environment against damage to coral reefs by the M.V. cruise ship. Caledonian Sky according to international law in accordance with UNCLOS 1982 article 194 paragraphs (1) and (2) concerning measures to prevent, reduce and control pollution of the marine environment. According to national laws protecting the marine environment against damage to coral reefs by the cruise ship M.V. Caledonian Sky is regulated in laws concerning the protection of the marine environment and applies in Indonesia. Second, Cruise Ship Legal Liability M.V. Caledonian Sky for Damage to Coral Reefs according to international law is regulated in UNCLOS 1982 Article 193 concerning the sovereign rights of the State to exploit its natural resources and Article 235 concerning responsibility and compensation obligations. According to national law, it is stipulated in laws concerning accountability and applies in Indonesia. Third, the London-based Noble Calidonia Company has acknowledged responsibility for this case. To prevent the occurrence by Caledonian Sky cruises, Indonesia must establish signs for certain areas to be used as shipping activities. Second, in upholding national law and international law in the supervision of marine waters in Indonesia, the government of the Republic of Indonesia must affirm and apply existing laws correctly and clearly in order to become a deterrent effect for ship operators and ship captains to prevent this kind of happening again in Indonesian marine. Third, in resolving cases of damage to coral reefs, Law Number 32 of 2009 concerning Environmental Protection and Management, Article 87 paragraphs (1) and (2) can be used.